HUBUNGAM MUTU PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN RAWAT JALAN UPT PUSKESMAS GANDRUNGMANGU I KABUPATEN CILACAP - -, safrudin; -, Ngisom; Yuwono, Tulus Aji (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
Quality of health service is perfection in health service that bringssatisfaction to patients which basically an effort to fulfill needs anddemand of customers of health service. Patient satisfaction which isrelated to quality of health service is average satisfaction of thepopulation and one of indicators of quality of service of health centers asreflected in the number of visits of patients. In 2008 visits toGandrungmangu I Health Center decreased. In average there were 2685visits whereas in 2007 there were 2896 visits. The decrease was about0,09%. This may due to some factors. The result of preliminaryobservation at Gandrungmangu I Health Center held in Januari 11-16,2010 to 30 patients at the health center showed 12 patients (40%)complained about long waiting time, 9 patients (30%) complained aboutstaff being late and 7 patients (23,3%) complained about unavailability ofdoctors.The study was to find out association between quality of healthservice and patient satisfaction. The study was expected to be used asconsideration in making decision to improve quality of health service atGandrungmangu I Health Center. The study was descriptive analyticalthat used 252 samples of Gandrungmangu I Health Center taken withsimple random sampling technique. Data were obtained in Juli 2010through questionnaire on quality and patient satisfaction. Data analysisused Spearman Rho.The majority (51,6%) of respondents said that quality of service ofGandrungmangu I Health Center was good in aspects of tangibles,reliability, responsiveness, assurance and empathy. The majority (64,3%)of respondents said that they felt satisfied after they got health servicefrom Gandrungmangu I Health Center in aspects of tangibles, reliability,responsiveness, assurance, and empathy. Statistically there wasassociation between quality of health service and patient satisfaction atGandrungmangu I Health Center where by P=0.000 < Î± = 0.05. Therewas association between quality of health service and patientsatisfaction.Keywords: quality of service, health service, patient satisfaction